Game Development With Python: Let’s Build a Simple Games! - Mochammad Gendry Afriansyah; Sandhi Alfianda Ghifari; Muhammad Taqi Wijdan; Rifki Syarif Hidayat; Muhammad Ni’am Syukri; Nurvelly Rosanti; Mirza Sutrisno; Sitti Nurbaya Ambo; Yana Adharani; Popy Meilina (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
The development of technology opens up opportunities for individuals to develop new skills, including in the increasingly popular game industry. To provide a basic understanding of game development, a Webinar and Workshop entitled “Game Development With Python: Let's Build a Simple Game!”. This activity consists of material presentation sessions in the Webinar and hands-on practice in the Workshop. Evaluation through questionnaires showed positive responses to the presenters and the material presented. Of the 37 participants who participated, the Pre-Test and Post-Test results showed an increase in understanding with an average initial score of 67.3% which increased to 89.4%. A total of 67.6% of participants expressed very satisfied, while 32.4% were satisfied. These results show that this activity succeeded in increasing participants' understanding and skills in developing simple games using Python, as well as making a positive contribution to students and the general public.